Antecedents of turnover intention among Gen z in Vietnam: The mediating role of affective commitment - Duc Anh Do; Quynh Diem Doan; Linh Khanh Vu; Thu Thi Le; Nguyet Minh Tran; Giang Linh Nguyen (Cogent Business & Management, 2023)
Turnover intention (TI) in many countries has been widely discussed, but research on the turnover intention by Gen Z in Vietnam is still in its infancy. This study examines the role of affective commitment (AC) as a mediator in the relationship between job satisfaction (JOS), emotional exhaustion (EE), and TI. A survey dataset with 602 observations was primarily collected from major cities in Vietnam, and partial least squares structural equation modeling (PLS-SEM) was applied. The results indicate that AC is closely related to EE. Moreover, EE has a significant direct impact on TI. However, unlike previous studies, no direct relationship was found between JOS and TI for Gen Z in Vietnam. Given the increasing number of new small and medium-sized businesses in Vietnam, this study contributes significantly to helping organizations plan more rational human resource policies.
Keywords: 650; affective commitment; emotional exhaustion; Gen Z; job satisfaction; turnover intention